Pengaruh health education tentang menstruasi terhadap tingkat kecemasan menghadapi menarche pada siswi - Sari, Nur Atika; Yuliana, Dewi; Puspita, Richta (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Menarche is the first menstruation experienced by a woman. Anxiety about menarche can occur because young women do not know the steps to take when they menstruate. Through the health education provided, it is hoped that individuals, families, and communities can experience changes in the way they think, act, and behave so that they can help overcome existing problems. Purpose: To determine whether there is an influence of health education about menstruation on the level of anxiety of female students facing menarche. Methods: Quantitative research with Pre-experimental Design research design and One Group Pretest and Posttest design. The sample in this study amounted to 30 female students with a sampling technique using Non-Probability Sampling through the Total Sampling technique. The analysis test used univariate and bivariate analysis using the Wilcoxon test. Results: Wilcoxon test analysis shows the influence of health education about menstruation in female students on the level of anxiety in facing menarche with a p-value = 0.000, which means p-value <0.05. Conclusion:  There is an influence of health education about menstruation on the level of anxiety in facing menarche in female students.   Keywords:Anxiety; Health Education; Menarche   Pendahuluan: Menarche adalah menstruasi pertama yang dialami seorang Perempuan. Kecemasan menghadapi menarche dapat terjadi karena remaja putri tidak mengetahui langkah yang harus diambil saat mengalami menstruasi. Melalui pendidikan kesehatan yang diberikan, diharapkan individu, keluarga, dan masyarakat bisa mengalami perubahan dalam cara berfikir, cara bersikap, dan cara berperilaku sehingga bisa membantu mengatasi masalah yang ada. Tujuan: Untuk mengetahui apakah ada pengaruh health education tentang menstruasi terhadap tingkat kecemasan siswi menghadapi menarche. Metode: Penelitian kuantitatif dengan desain penelitian Pre-experimental Design dan rancangan One Group Pretest dan Posttest. Sampel pada penelitian ini berjumlah 30 siswi dengan teknik pengambilan sampling menggunakan Non-Probability Sampling melalui teknik Total Sampling. Uji analisis menggunakan analisis univariat dan bivariat yang menggunakan uji Wilcoxon. Hasil: Analisis uji wilcoxon terdapat pengaruh health education tentang menstruasi pada siswi terhadap tingkat kecemasan menghadapi menarche dengan p-value = 0.000 yang artinya p-value<0.05. Simpulan: Terdapat pengaruh health education tentang menstruasi terhadap tingkat kecemasan menghadapi menarche pada siswi.   Kata Kunci: Health Education; Kecemasan; Menarche.